PENGARUH KEPUASAN NASABAH TERHADAP KUALITAS LAYANAN PEMBIAYAAN MIKRO ARRUM EMAS DI PEGADAIAN KCP PADALARANG, BANDUNG BARAT - Nur Aisyah Arya Agung, Ratu Aisyah; Maryati, Maryati; Ismiyanti, Nina (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
Customer satisfaction is the evaluation of consumers against the suitability between actual conditions and their expectations. This study aims to measure the influence of customer satisfaction on the quality of Arrum Emas product financing services. The research method used is a quantitative approach with a survey using a questionnaire. The research population consisted of 577 customers, with a purposive sample of 85 respondents. The results of the study showed that customer satisfaction reached 81.72%, which was included in the very good category. The quality of financing services is also high, at 82.25%, which shows an increase in the number of customers at PT Pegadaian KCP Padalarang, West Bandung. Data analysis showed a significant relationship between customer satisfaction and financing service quality, with a significance value of 0.000 (p<0.05) and a correlation coefficient (R) of 0.951, which showed a strong influence. An R Square value of 0.35 means that 35% of the variation in the quality of financing services is explained by customer satisfaction, while 65% is explained by other factors. The significance test showed that the t-count (6.679) was greater than the t-table (1.663), with a significant value of 0.000 below the alpha of 0.05. This means that there is a significant positive influence of customer satisfaction on the quality of financing services at PT Pegadaian KCP Padalarang, West Bandung. Thus, alternative hypotheses were accepted, showing a significant difference between the average customer satisfaction and the quality of financing services.